Pancreatic Cancer and Thrombosis - Shah, Manasi M; Saif, Mumhammad Wasif (JOP. Journal of the Pancreas, 2010)
Although pancreatic cancer is recognized as a major risk factor for venous thromboembolism, the exact magnitude of the problem is not known. The incidence varies from 17% to 57% depending on different studies. The effect of venous thromboembolism on outcomes in not well defined and there is no known independent predictor of survival. This review is an update from the current American Society of Clinical Oncology (ASCO) Annual Meeting regarding the impact of thrombotic events on the clinical outcomes, the association of tissue factor and thrombotic events, and the primary prevention of venous thromboembolism in pancreatic cancer patients undergoing active treatment. Image: University of Connecticut Health Center. Farmington, CT, USA